2020
DOI: 10.7717/peerj.9789
|View full text |Cite
|
Sign up to set email alerts
|

Range reduction of Oblong Rocksnail,Leptoxis compacta, shapes riverscape genetic patterns

Abstract: Many freshwater gastropod species face extinction, including 79% of species in the family Pleuroceridae. The Oblong Rocksnail, Leptoxis compacta, is a narrow range endemic pleurocerid from the Cahaba River basin in central Alabama that has seen rapid range contraction in the last 100 years. Such a decline is expected to negatively affect genetic diversity in the species. However, precise patterns of genetic variation and gene flow across the restricted range of L. compacta are unknown. This lack of information… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…Observed spatial genetic diversity in P. foremani was similar to riverscape genetic patterns seen in previously studied pleurocerids ( Whelan et al 2019 ; Wright et al 2020 ). This was surprising because the 2 previous population genomic studies on pleurocerids focused on species from one of the least modified major rivers in the southeastern United States.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Observed spatial genetic diversity in P. foremani was similar to riverscape genetic patterns seen in previously studied pleurocerids ( Whelan et al 2019 ; Wright et al 2020 ). This was surprising because the 2 previous population genomic studies on pleurocerids focused on species from one of the least modified major rivers in the southeastern United States.…”
Section: Discussionsupporting
confidence: 82%
“…For example, L. ampla populations in tributaries of the Cahaba River in central Alabama displayed lower levels of genetic diversity, on average, than mainstem populations ( Whelan et al 2019 ). Furthermore, Wright et al (2020) found that Leptoxis compacta , a species restricted to the mainstem Cahaba River, had relatively high levels of genetic diversity when compared with tributary populations of L. ampla , and our results show similarity with spatial genetic diversity in P. foremani . Thus, low genetic diversity of P. foremani in Yellowleaf Creek compared with Lake Mitchell and the Coosa River at Wetumpka is likely the result of natural processes.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations